Is it just me? : or is it nuts out there? - Goldberg, Whoopi, 1955- (Hyperion Books, 2010)
Have you noticed that things aren't as civil as they once were? Or that rudeness is no longer an exception but a lifestyle? Sure you have. All you need to do is set foot outside your door to see that bad manners are taking over everywhere. People are yakking on cell phones in restaurants, even at church. Folks in carpools wear enough cologne to make our eyes bleed. Complete strangers think it's OK to rub a pregnant lady's belly. Passengers abuse flight attendants, family outings to the ball park are ruined by rowdy drunks, a congressman heckled the President of the United States. Well, the author, a well-known comedienne and film star has noticed all this and more and asked herself, "Is it just me?" Unleashing her trademark irreverence and humor, her new book of observations takes a funny and excruciatingly honest look at how a loss of civility is messing with the quality of life for all of us. So if your pet peeve is folks who talk in movie theaters like it was their living room, or if you get bugged by people clipping their nails and performing other personal hygiene next to you on the bus, or if you cringe when "please" and "thank you" get replaced by "gimme" and "huh?", you have found a kindred spirit. The author has witnessed the growing disrespect and rudeness in our lives and realized she is not alone; and, as you'll discover in these pages, neither are you.